The conserved long non-coding RNA CARMA regulates cardiomyocyte differentiation. Issue 10 (30th August 2021) - Kay, Maryam; Soltani, Bahram M; Nemir, Mohamed; Aghagolzadeh, Parisa; Pezzuto, Iole; Chouvardas, Panagiotis; Ruberto, Francesco; Movahedi, Fatemeh; Ansari, Hassan; Baharvand, Hossein; Pedrazzini, Thierry
Abstract: Aims: Production of functional cardiomyocytes from pluripotent stem cells requires tight control of the differentiation process. Long non-coding RNAs (lncRNAs) exert critical regulatory functions in cell specification during development. In this study, we designed an integrated approach to identify lncRNAs implicated in cardiogenesis in differentiating human embryonic stem cells (ESCs). Methods and results: We identified CARMA ( CARdiomyocyte Maturation-Associated lncRNA ), a conserved lncRNA controlling cardiomyocyte differentiation and maturation in human ESCs. CARMA is located adjacent to MIR-1-1HG, the host gene for two cardiogenic miRNAs: MIR1-1 and MIR-133a2, and transcribed in an antisense orientation. The expression of CARMA and the miRNAs are negatively correlated, and CARMA knockdown increases MIR1-1 and MIR-133a2 expression. In addition, CARMA possesses MIR-133a2 binding sites, suggesting the lncRNA could be also a target of miRNA action. Upon CARMA down-regulation, MIR-133a2 target protein-coding genes are coordinately down-regulated. Among those, we found RBPJ, the gene encoding the effector of the NOTCH pathway. NOTCH has been shown to control a binary cell fate decision between the mesoderm and the neuroectoderm lineages, and NOTCH inhibition leads to enhanced cardiomyocyte differentiation at the expense of neuroectodermal derivatives. Interestingly, two lncRNAs, linc1230 and linc1335, which are known repressors of neuroectodermal specification, were found up-regulated upon Notch1 silencing in ESCs. Forced expression of either linc1230 or linc1335 improved ESC-derived cardiomyocyte production. These two lncRNAs were also found up-regulated following CARMA knockdown in ESCs. Conclusions: Altogether, these data suggest the existence of a network, implicating three newly identified lncRNAs, the two myomirs MIR1-1 and MIR-133a2 and the NOTCH signalling pathway, for the coordinated regulation of cardiogenic differentiation in ESCs. Graphical Abstract: